Analysis of Glucose Levels in White Glutinous Rice Bran: A Systematic Literature Review - Himyatul Hidayah; Musfiroh, Eka Nurfarida; Fadia Ainun Sathi’ah; Shintya Happy Herawati (HM Publisher, 2024)
White glutinous rice bran has lower glucose levels than white glutinous rice. This could be relevant for glycemic management in diabetes sufferers. Lower glucose levels can help reduce blood sugar spikes after food consumption. White glutinous rice bran, with its low glucose content, can be considered a safe and beneficial food alternative for diabetes sufferers. The literature search process was carried out on various databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar) regarding the analysis of glucose levels in white glutinous rice bran. This study follows the preferred reporting items for systematic reviews and meta-analysis (PRISMA) recommendations. The glucose content in rice bran ranges from 1.5 to 2.5%, a lower value compared to the glucose content in white glutinous rice which reaches around 7.5%. White glutinous rice bran has relatively low glucose levels, making it a potential food option for consumption by diabetes mellitus sufferers.